The Renascence of Hebrew Literature (1743-1885) - Slouschz, Nahum, 1872-1966 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Renascence of Hebrew Literature (1743-1885)" by Nahum Slouschz is a historical account likely written in the early 20th century. This work aims to explore the revival and development of modern Hebrew literature, challenging the notion that Hebrew had become a dead language devoid of literary vitality. It covers the significant movements and figures in Jewish literary history during that period, highlighting the intellectual struggles and cultural transformation of Jewish communities. The opening of the work establishes the context that Hebrew literature had been dismissed for centuries as irrelevant, overshadowed by a deeply ingrained reliance on other vernaculars among Jewish populations. Slouschz presents the surprising emergence of modern Hebrew literature amidst socio-political upheavals and the quest for cultural identity, noting the efforts of various authors and intellectuals who strove to articulate a new literary vision. By tracing the evolution of Hebrew literature and its socio-cultural implications, Slouschz sets the stage for a deeper exploration of individual authors and movements in subsequent chapters. (This is an automatically generated summary.)
In Italy. Moses Hayyim Luzzatto -- In Germany. The Meassefim -- In Poland and Austria. The Galician school -- In Lithuania. Humanism in Russia -- The romantic movement. Abraham Mapu -- The emancipation movement. The realists -- The conflict with Rabbinism. Judah Leon Gordon -- Reformers and conservatists. The two extremes -- The national progressive movement. Perez Smolenskin -- The contributors to Ha-Shahar -- The novels of Smolenskin -- Contemporaneous literature -- Conclusion.
Release date is 2005-02-01
Produced by Charles Aldarondo, Tiffany Vergon, Blain Nelson and the Online Distributed Proofreading Team
Keywords: Hebrew literature, Modern -- History and criticism